The Red Years of Cahiers du cinéma (1968-1973) : Volume I, Ideology and Politics - Fairfax, Daniel (Book collections on Project MUSE., 2021)
The uprising which shook France in May 1968 also had a revolutionary effect on the country's most prominent film journal. Under editors Jean-Louis Comolli and Jean Narboni, 'Cahiers du cinema' embarked on a militant turn that would govern the journal's work over the next five years. With a Marxist orientation inspired by the thinking of Louis Althusser, Jacques Lacan and Roland Barthes, the "red years" of 'Cahiers du cinema' produced a theoretical outpouring that was formative for the establishment of film studies as an academic discipline in the 1970s, and is still of vital relevance for the contemporary audiovisual landscape. It was also the seminal experience for a generation of critics who have dedicated the following half-century to the task of critically responding to the cinema. 00'The Red Years of Cahiers du Cinema (1968-1973)' gives a historical overview of this period in the journal's history, combining biographical accounts of the critics who were involved with Cahiers in the post-1968 and theoretical explorations of the text they wrote.